School Principal's Leadership Strategy in Improving Teacher Professionalism in Special Schools (SLB) Negeri 1 Makassar, Makassar City - Kurniawan Kurniawan; Misykat Malik Ibrahim; Yuspianti Yuspianti (Journal of Pedagogi, 2024)
This study aims to analyze the principal's leadership strategy in improving teacher professionalism in SLB Negeri 1 Makassar City. Using a qualitative approach with a phenomenological method, data were collected through interviews, observations and documentation from various related parties. The results showed that principals play an important role in improving teacher professionalism to support quality education for students with special needs. The leadership strategies implemented include specialized training, implementing effective teaching methods and developing an adaptive curriculum according to students' needs. Principals play the role of educator, leader, manager, motivator and supervisor, which is realized in efforts to improve teacher professionalism. Supporting factors include the high level of education of teaching staff (S1 to S3), dedication, discipline, and adequate facilities. The obstacle faced is the lack of competence of some teachers in IT knowledge. The implication is that school principals are expected to be more dedicated in creating a conducive educational environment, routinely monitoring and evaluating the learning process, and improving infrastructure. Teachers are expected to carry out their obligations as educators well, and continue to improve their professional, social, pedagogical and personality competencies to achieve educational goals